Creep and drying shrinkage behaviour of crumb rubber concrete (CRC). Issue 2 (2nd July 2020) - Li, Danda; Zhuge, Yan; Gravina, Rebecca; Benn, Tom; Mills, Julie E.
ABSTRACT: Creep and drying shrinkage behaviour of CRC was investigated through experimental tests on a series of three stacked cylindrical specimens of 100 mmx200 mm. Constant load was maintained on the specimens for duration of 659 days. For investigation of the influence of the rubber particle treatment method on the CRC creep and shrinkage behaviour, both NaOH-treated and untreated CRC with 18% rubber replacement by volume of sand were considered, with traditional concrete (TC) as a reference mix. Test results of the three mixes were analysed and compared. Creep prediction models and creep coefficients for TC from five standards were considered and comparisons between these models and the experimental results were made. Test results showed that both CRC mixes showed a higher drying shrinkage than TC. NaOH-treatment on rubber particles had a slight positive effect on the long-term shrinkage control of CRC material. The addition of rubber particles to the concrete mix did not affect the concrete creep significantly in the long term. The effect of rubber pre-treatment on creep could be ignored. Both the drying shrinkage and creep coefficient results for all concrete groups were within the limits of AS3600 model.